Dynamic left ventricular changes in patients with gestational diabetes: A speckle tracking echocardiography study. Issue 1 (28th September 2016) - Meera, Srinidhi J.; Ando, Tomo; Pu, Daniel; Manjappa, Shivaprasad; Taub, Cynthia C.
ABSTRACT: Purpose: The left ventricle (LV) undergoes physiologic remodeling in adaptation to the hemodynamic changes that occur in pregnancy. Speckle tracking echocardiography (STE) is a novel and reliable tool to evaluate subtle myocardial alterations that have been utilized to assess myocardial changes in patients with diabetes mellitus (DM) but not in patients with gestational DM (GDM). We seek to evaluate changes in LV function using STE in patients with GDM compared with women with normal pregnancy. Methods: This was a single‐center retrospective cohort study. A total of 312 pregnant patients that underwent transthoracic echocardiogram (TTE) between 2009 and 2014 were screened. After excluding patients with comorbidities or insufficient data, 90 women were included. TTE from the second and third trimester for each patient were then reviewed, and STE analysis was performed. Results: Of the 90 subjects, 72 had normal pregnancies and 18 developed GDM. There was no difference in LV end‐diastolic diameter (4.73 ± 0.40 versus 4.60 ± 0.56, p = 0.25), LV end‐systolic diameter (3.12 ± 0.35 versus 2.91 ± 0.61, p = 0.152), or ejection fraction (62.26 ± 4.12 versus 63.50 ± 5.24, p = 0.314) between the two groups. Global longitudinal strain was lower (−19.8 ± 3.34 versus −17.2 ± 2.18, p < 0.001) in patients with GDM, while time‐to‐peak strain was greater (0.43 ± 0.05 versus 0.50 ± 0.06, p < 0.001). Circumferential and radial strains were preserved in both groups. Conclusions: Although conventional TTE variables show preserved LV size and function, LV longitudinal strain suggests subclinical myocardial dysfunction in patients with GDM. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :20–27, 2017